Análise do contexto de produção do texto de um referencial curricular oficial de química para o ensino médio em Goiás - Ribeiro Júnior, Ramon Marcelino (2013)
The curriculum has occupied a prominent place in the landscape of contemporary educational reforms. In this work we focus on the production of a referential official curriculum of chemistry to secondary education in the State of Goiás. Throughout our investigation we relayed on studies that: a) had the objective to discuss aspects related to the purpose of teaching chemistry in secondary education, with emphasis on authors from Science/Chemistry education community; b) conduct discussions on curricular concepts, highlighting authors of the curriculum field; c) develop curriculum using research to theoretical and methodological approach of the continuous cicle of policies. The prospect of a continuous cicle policy is designed from the intertwining of texts / discourses that circulate among three basic contexts: the context of influence; context of defining texts, and practice context. In the policy cicles the texts / discourses are understood as product from social interactions, understood as relations of power , and are associated with different sets of meanings that articulate and fit into a greater or lesser degree , by recontextualizing processes in different contexts through which they circulate. The construction of the data was performed from the recording and transcript from the meeting of defining texts context, our analytical focus. We identified and examined three discourses privileged in the process of negotiating meanings of the proposal 1) discourse about the purposes of teaching chemistry, 2) discourse on the concepts of curriculum and 3) discourse about the criteria for selection and organization of content. We also highlight aspects of the movement of recontextualization internal context of defining texts, comparing the configuration of the first discursive formulations, developed in design meetings, those present in the final version given to curricular referential We conclude that :i) there is the attempt to articulate different purposes for teaching chemistry , with emphasis on the purpose of education for critical citizenship; ii) there is a defense of a broad conception of curriculum affiliated with the critical perspective , discourse that implies defense of a construction of a hybrid proposal between orientation and prescription , with a predominance of the first and critical of the way driving educational reform in the State; iii) the selection criteria adopted are of the "basic content" and "minimum contents" . The contents are organized by a conceptual bias, and articulated a design approach that takes learning to necessarily partial and can be performed at various levels of complexity. We also conclude that when considering the historicity and contingency associated curricular productions we giving it the status of “eternal challenge ".